IS-19 Biosecurity Matters! Protect Your Research - Ibrahim Faseeh (Hemera Zoa, 2018)
Genetically modified mammals are an essential tool in today’s biomedical research resulting in a global trade where biosecurity is critical at the national, sub-national, and perhaps most importantly at an institutional level. The global research animal exchange entails many risks to the microbial status of research animals and animal colonies. Though research animal vendors have well-established procedures to minimise biosecurity concerns, the typical researcher may need guidance in addressing biosecurity concerns when importing animals from a vendor or colleague or when shipping animals to a colleague. A biosecurity risk mitigation process typically involves careful evaluation of animal source risk, transportation risks and destination institution capability and researcher’s requirements. This presentation will focus on important considerations when developing a plan, meeting a given institution’s biosecurity needs when receiving animals from across town or around the world while facilitating the animal related researcher’s needs.